AN APPLICATION OF AN DISCOURSE-BASED APPROACH IN TEACHING ENGLISH READING SKILL AT THANH HOA VOCATIONAL SCHOOL OF COMMERCE-TOURISM - Nguyễn, Thị Ngọc (University of Languages and International Studies, 2017)
The study was conducted to investigate the effectiveness of the application of a discourse-based approach in teaching English reading skill at Thanh Hoa Vocational School of Commerce-Tourism. The specific objectives of the study are: To find out changes in (...)